Effect of Trailing Heat Sink, Filler Type, and Current Variation on Distortion in GMAW Welding of Stainless Steel 304 - IMAH LULUK KUSMINAH; Mukhlis Mukhlis Mukhlis (Politeknik Negeri Lhokseumawe, 2025)
The use of welding technology in the manufacturing industry has become increasingly widespread due to its ability to enhance production effectiveness and efficiency. Stainless steel 304 is commonly used in industrial applications but is highly sensitive to weld-induced thermal expansion, making it prone to distortion. Such distortion is considered detrimental as it leads to deformation of the design, reduced dimensional accuracy, decreased mechanical strength, and increased costs for welded product repairs. To address this issue, a study was conducted using trailing heat sink-assisted welding. The Gas Metal Arc Welding (GMAW) method was applied with variations in filler electrodes (ER316LSi and ER308LSi) and welding currents (100 A and 120 A). The welding results were visually inspected and distortion was measured. The findings indicate that welding with a trailing heat sink can effectively reduce distortion, particularly at higher current levels.